2021
DOI: 10.1371/journal.ppat.1009819
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of methylglyoxal by the glyoxalase system is required for glutathione availability and virulence activation in Listeria monocytogenes

Abstract: Listeria monocytogenes is a Gram-positive, food-borne pathogen that lives a biphasic lifestyle, cycling between the environment and as a facultative intracellular pathogen of mammals. Upon entry into host cells, L. monocytogenes upregulates expression of glutathione synthase (GshF) and its product, glutathione (GSH), which is an allosteric activator of the master virulence regulator PrfA. Although gshF mutants are highly attenuated for virulence in mice and form very small plaques in host cell monolayers, thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Furthermore, depletion of glucose from cell culture media reverses the sensitivity of a gloA mutant in these neutrophils, emphasizing the importance of glycolysis in the production of one or more toxic metabolites. More recently, Portnoy and co-workers [ 44 ] showed that mutants of Listeria monocytogenes lacking GloA are highly attenuated in mice. Because this phenotype is rescued by constitutive activation of PrfA, a bacterial transcription factor activated upon entry into host cell cytosol, the authors speculate that host-derived MG is a cue that bacteria sense to activate transcription of virulence genes.…”
Section: Aldehydes Beyond Mycobacterium Tuberculosis ...mentioning
confidence: 99%
“…Furthermore, depletion of glucose from cell culture media reverses the sensitivity of a gloA mutant in these neutrophils, emphasizing the importance of glycolysis in the production of one or more toxic metabolites. More recently, Portnoy and co-workers [ 44 ] showed that mutants of Listeria monocytogenes lacking GloA are highly attenuated in mice. Because this phenotype is rescued by constitutive activation of PrfA, a bacterial transcription factor activated upon entry into host cell cytosol, the authors speculate that host-derived MG is a cue that bacteria sense to activate transcription of virulence genes.…”
Section: Aldehydes Beyond Mycobacterium Tuberculosis ...mentioning
confidence: 99%
“…More broadly, aldehydes may also have a role in the defense against other microbes. For example, a recent report by the Portnoy lab showed that in Listeria monocytogenes (L. monocytogenes ), MG activates transcription of glutathione (GSH) synthase-encoding gene gshF , leading to increased GSH production and thereby activating the master virulence regulator PrfA (52). A L. monocytogenes mutant that lacks a gene encoding glyoxalase A, a key enzyme in methylglyoxal detoxification, has decreased GSH levels in vitro and is attenuated for infection.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of GSH could be calculated by subtracting the amount of GSSG from the total glutathione (GSSG + GSH). GSH concentrations of the parental and mutant strains were measured as described above ( Anaya-Sanchez et al, 2021 ). A 96-well plate was used for measurement, and the standards and samples were added in sequence.…”
Section: Methodsmentioning
confidence: 99%